PENERAPAN MODEL PEMBELAJARAN STEM UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR NEGERI 020 RIDAN PERMAI - Suci Amalia; Ramdhan Witarsa; Nurmalina Nurmalina (Jurnal Muassis Pendidikan Dasar, 2023)
This study aims to improve the critical thinking skills of fourth graders of Public Elementary School 020 Ridan Permai with the STEM learning model. This research was conducted at SDN 020 Ridan Permai. The subjects used were 23 students consisting of 12 male students and 11 female students. The research method used was Classroom Action Research which was conducted in two cycles, each cycle consisting of two meetings. The data collection instrument was carried out by a thinking skills test critical, teacher and student observation sheets as the level of implementation and achievement in using the STEM learning model. Data analysis techniques were carried out in qualitative and quantitative descriptions. Based on the results of data analysis, it can be seen that there is an increase in students' critical thinking skills in science content. Preliminary data in cycle I meeting I was 35%, cycle I meeting II increased to 57% then in cycle II meeting I increased to 73%, and cycle II meeting II increased again to 87%. Thus it can be concluded that the STEM learning model can improve the critical thinking skills of class IV students at SDN 020 Ridan Permai.